2009
DOI: 10.1136/hrt.2008.146589
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation in mainland China: epidemiology and current management

Abstract: With the economic development of China, research in atrial fibrillation has improved progressively, but due to a lack of international communication, many significant achievements have not been widely recognised. A brief overview of epidemiology, current therapy and research on atrial fibrillation in mainland China is provided. Chinese electrophysiologists would like to contribute more to international research in cardiac electrophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 21 publications
2
22
1
Order By: Relevance
“…Another study produced a crude AF prevalence rate of 0.77% and an age-adjusted rate of 0.61%, suggesting that approximately 8 million adults in China have AF [16,17]. AF is surely a substantial public health burden in China [18].…”
Section: Prevalence Of Cvd In Chinamentioning
confidence: 98%
“…Another study produced a crude AF prevalence rate of 0.77% and an age-adjusted rate of 0.61%, suggesting that approximately 8 million adults in China have AF [16,17]. AF is surely a substantial public health burden in China [18].…”
Section: Prevalence Of Cvd In Chinamentioning
confidence: 98%
“…In contrast, a German AF registry—the Central Registry of German Competence Network on Atrial Fibrillation (AFNET)—demonstrated that only 21.3% of patients received antiarrhythmic medication, but 53.4% received electrical or pharmacologic cardioversion and 5% underwent AF ablation . Chinese data demonstrated variable use of rate‐control treatments, partly dependent on the AF phenotype . Among those with paroxysmal AF, 44% of patients received rate‐control treatment, compared to 83% of patients with permanent AF.…”
Section: Global Trends and Differences In Af Treatmentsmentioning
confidence: 99%
“…Among multiple risk factors, age is a major contributor to the increase in AF prevalence . Epidemiological studies showed that over 1.83% of Chinese AF patients were older than 60 years, while 7.5% were older than 80 years . While life expectancy has been extended following the economic upturn in China, the increasing numbers of geriatric individuals, and those suffering from AF makes the management of AF a major public health concern.…”
Section: Introductionmentioning
confidence: 99%